Understanding farmers’ access and perception to Islamic microfinance on agricultural financing: study in Central Lampung regency - Budi Yoko; Adistiar Prayoga (Journal of halal product and research (JPHR), 2019)
The agricultural sector is a major sector in economic activity in the province of Lampung. However, the crucial issues are still encountered in the agricultural sector, such as low productivity triggered by a narrow land ownership and restrictions on capital. Baitul Maal wat Tamwil (BMT) is one example of rural microfinance institutions that can be optimized role in improving farmers' access to financing sources. The purpose of this study was to identify the perceptions of farmers on the existence of BMT and identify factors that can increase the chances of farmers access the agricultural financing of BMT. The results of the analysis has pointed out that farmers assess the perception of the existence of BMT important role in supporting farming activities or other economic activity. In terms of employee services, facilities and infrastructure owned, as well as agricultural finance products from BMT, farmers assess it is already quite good. Farmers give agreed statements to each perception attribute with different percentages. The results of the analysis with the logistic regression model show that the significant variables to increase farmers' opportunities to access sharia agricultural finance from BMT are the distance of farmer's house to BMT service office, cost of fund, and farmer's view of the credit interest system.